2016
DOI: 10.1038/ncomms11579
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and clinical significance of ESR1 mutations in ER-positive metastatic breast cancer patients receiving fulvestrant

Abstract: Mutations in ESR1 have been associated with resistance to aromatase inhibitor (AI) therapy in patients with ER+ metastatic breast cancer. Little is known of the impact of these mutations in patients receiving selective oestrogen receptor degrader (SERD) therapy. In this study, hotspot mutations in ESR1 and PIK3CA from ctDNA were assayed in clinical trial samples from ER+ metastatic breast cancer patients randomized either to the SERD fulvestrant or fulvestrant plus a pan-PI3K inhibitor. ESR1 mutations are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
222
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(244 citation statements)
references
References 37 publications
15
222
2
2
Order By: Relevance
“…Gain-of-function mutations in ESR1, the gene encoding the ER, are a relatively rare event in primary breast cancer (Cancer Genome Atlas Network 2012), but can be detected using next-generation sequencing in approximately 20% of patients with metastatic ER-positive disease who had received prior endocrine therapies , Toy et al 2013, Jeselsohn et al 2015. A higher prevalence (up to 55%) of ESR1 mutations has been reported in circulating free DNA (cfDNA) in metastatic ER-positive breast cancers with prior AI therapy when using digital droplet PCR to increase mutation detection sensitivity (Chandarlapaty et al 2016, Fribbens et al 2016, Spoerke et al 2016. These mutations cluster in the ligand-binding domain of the ER and lead to ligand-independent ER activity that promotes tumour growth, partial resistance to endocrine therapy and potentially enhanced metastatic capacity.…”
Section: Endocrine-related Cancer (2016) 23 T227-t241mentioning
confidence: 99%
“…Gain-of-function mutations in ESR1, the gene encoding the ER, are a relatively rare event in primary breast cancer (Cancer Genome Atlas Network 2012), but can be detected using next-generation sequencing in approximately 20% of patients with metastatic ER-positive disease who had received prior endocrine therapies , Toy et al 2013, Jeselsohn et al 2015. A higher prevalence (up to 55%) of ESR1 mutations has been reported in circulating free DNA (cfDNA) in metastatic ER-positive breast cancers with prior AI therapy when using digital droplet PCR to increase mutation detection sensitivity (Chandarlapaty et al 2016, Fribbens et al 2016, Spoerke et al 2016. These mutations cluster in the ligand-binding domain of the ER and lead to ligand-independent ER activity that promotes tumour growth, partial resistance to endocrine therapy and potentially enhanced metastatic capacity.…”
Section: Endocrine-related Cancer (2016) 23 T227-t241mentioning
confidence: 99%
“…These findings highlight the need for a novel SERD that can bind and inhibit both wild-type and mutant forms of ER in order to more effectively treat this patient population. Recent clinical data have demonstrated that while the presence of ESR1 mutations can be a prognostic indicator of AI resistance, the extent of fulvestrant efficacy is not influenced by ESR1 status (32,33) …”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that patients with advanced breast cancer with ESR1 mutations at baseline have better survival when treated with fulvestrant [47]. Contradictory results have been published in a retrospective study, where ERS1 mutations detected by ctDNA did not change progression-free survival [48]. In addition, tumor volume in responders to neoadjuvant chemotherapy was shown to be related to the methylation of five genes (BRCA1, MGMT, GSTP1, stratifin, and MDR1) [49].…”
Section: Clinical Applications Of Liquid Biopsies In Breast Cancermentioning
confidence: 67%